Ah! Management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
On 11 February 2003, the Management for Development Foundation of The Netherlands opened a new management training office in Arusha, Tanzania. Its courses, scheduled to start towards the end of 2003, will include: Integral project cycle...